Editorial: On Cinema - Ribas, Daniel; Crespo, Nuno; Caires, Carlos Sena (Journal of Science and Technology of the Arts, 2020)
In the past decades, the field of cinema has undergone several transformations. The digital turn increasingly called for new forms of production, distribution, and exhibition, which imply different ways of thinking, doing, and experimenting cinema. These new forms also reduced the gap between cinema to other so-called visual arts. If cinema and visual arts were already in the process of merging, the last years forced the naturalization of thinking in similar theoretical grounds. This special issue aims to be a forum for the discussion of new practices of researching cinema, and the changes in cinema’s forms of experience and production.
Number: 2
Keywords: Art and cinema; Cinema; Contemporary cinema; Digital turn; Visual Arts

Enhancing Health and Public Health through Machine Learning: Decision Support for Smarter Choices - Rodrigues, Pedro Miguel; Madeiro, João Paulo; Marques, João Alexandre Lobo (Bioengineering, 2023)
In recent years, the integration of Machine Learning (ML) techniques in the field of healthcare and public health has emerged as a powerful tool for improving decision-making processes [...]
Number: 7 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: n/a

Modelling the barriers that are preventing e-commerce to thrive – a case study from Portugal, international journal of business excellence - Silva, Susana Costa e; Machado, Joana Costa; Martins, Carla; Duarte, Paulo; Marques, João Alexandre Lobo (International Journal of Business Excellence, 2021)
The identification of barriers for e-commerce to thrive in specific countries is a topic of great interest. This work proposes two models to study the barriers to B2C e-commerce adoption in Portugal, highlighting obstacles less exploited by previous research: the impact of offline shopping pleasure and the influence of the distance to shopping malls on online shopping intent. An online survey was conducted based on different constructs. A multivariate OLS hierarchical regression was used to analyse the proposed models regarding the intention to buy online and the number of online purchases. The results revealed that customer satisfaction is a strong predictor of intent to buy online and that perceived product risk remains a barrier to e-commerce. Consumers living in high urbanised areas have more propensity to buy online. Helpful information is provided regarding the impact of context, culture, product, and individual barriers, showing that multichannel strategies are best suited for success.
Keywords: E-commerce barriers; Online shopping; Portugal; Retail

The Political and Economic Dependence of the Press in Macao under Portuguese and Chinese Rule: Continuity and Change - Costa-Ribeiro, Nelson; Simões, José Manuel (Communication & Society, 2021)
The article analyses the media system in Macao, a special administrative region of China that transitioned from Portuguese to Chinese sovereignty in 1999, becoming one of cities in the world with the largest number of published newspapers per capita. Combining historical research with the analysis of contemporary empirical data collected through interviews with journalists working on the ground, the research demonstrates how there is a long tradition of state control that goes back to the colonial era and that has assumed different forms, ranging from outright censorship to physical intimidation of journalists and economic dependence on the government. Limitations and control strategies imposed on news reporting during the Portuguese administration continue to be practiced today by the Chinese authorities. Even so, journalists operating on the Macao media market tend to overstate the level of freedom they are given, which can be attributed to media outlets being economically dependent on the state. Nevertheless, the level of freedom attributed to the press is today higher than it had been during the colonial period with some critical voices being allowed to reach the media. This needs to be understood in the context of what has been defined as the Chinese safety valve strategy.
Number: 1
Keywords: Censorship; Journalism Practice; Media Systems; Press Freedom; Press Subsidies